Impact of Personal Protective Equipment on the Performance of Emergency Pediatric Tasks. Issue 12 (25th December 2021) - Adler, Mark D.; Krug, Steven; Eiger, Carmel; Good, Grace L.; Kou, Maybelle; Nash, Mark; Henretig, Fred M.; Hornik, Christoph P.; Gosnell, Leigh; Chen, Jia-Yuh; Debski, Julie; Sharma, Gaurav; et al.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: Personal protective equipment (PPE) is worn by health care providers (HCPs) to protect against hazardous exposures. Studies of HCPs performing critical resuscitation tasks in PPE have yielded mixed results and have not evaluated performance in care of children. We evaluated the impacts of PPE on timeliness or success of emergency procedures performed by pediatric HCPs. Methods: This prospective study was conducted at 2 tertiary children's hospitals. For session 1, HCPs (medical doctors and registered nurses) wore normal attire; for session 2, they wore full-shroud PPE garb with 2 glove types: Ebola level or chemical. During each session, they performed clinical tasks on a patient simulator: intubation, bag-valve mask ventilation, venous catheter (IV) placement, push-pull fluid bolus, and defibrillation. Differences in completion time per task were compared. Results: There were no significant differences in medical doctor completion time across sessions. For registered nurses, there was a significant difference between baseline and PPE sessions for both defibrillation and IV placement tasks. Registered nurses were faster to defibrillate in Ebola PPE and slower when wearing chemical PPE (median difference, −3.5 vs 2 seconds, respectively; P < 0.01). Registered nurse IV placement took longer in Ebola and chemical PPE (5.5 vs 42 seconds, respectively; P < 0.01). After the PPE session, participants were significantly less likely to indicate that full-body PPE interfered with procedures, was claustrophobic, or slowed them down. Conclusions: Personal protective equipment did not affect procedure timeliness or success on a simulated child, with the exception of IV placement. Further study is needed to investigate PPE's impact on procedures performed in a clinical care context.